2008
DOI: 10.1115/1.2795786
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Studies of the Flow Field Characteristics of Low-Swirl Injectors for Adaptation to Fuel-Flexible Turbines

Abstract: The low-swirl injector (LSI) is a simple and cost-effective lean premixed combustion method for natural-gas turbines to achieve ultralow emissions (<5 ppm NOx and CO) without invoking tight control of mixture stoichiometry, elaborate active tip cooling, or costly materials and catalysts. To gain an understanding of how this flame stabilization mechanism remains robust throughout a large range of Reynolds numbers, laboratory experiments were performed to characterize the flowfield of natural-gas flames at si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 17 publications
6
23
0
Order By: Relevance
“…One of FutureGen's key components is a cost-competitive hydrogen turbine with ultra low NO x emission and high efficiency. The goal of our research is to adapt our lean premixed low-swirl injector (LSI) [1][2][3][4] to the H 2 turbines.…”
Section: Introductionmentioning
confidence: 99%
“…One of FutureGen's key components is a cost-competitive hydrogen turbine with ultra low NO x emission and high efficiency. The goal of our research is to adapt our lean premixed low-swirl injector (LSI) [1][2][3][4] to the H 2 turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the velocity measurements show that the LSI flowfield exhibits self-similarity behavior. Two parameters deduced from the centerline velocity profiles are invoked to characterize self-similar behavior [13,14]. They are the virtual origin of the divergent flow, x 0, and the non-dimensional axial aerodynamic stretch rate, a x .…”
mentioning
confidence: 99%
“…Additionally, the present nozzle configuration is more similar to the jet-LSB than the vane-LSI. The jet-LSB data showed deviations from the linear turbulent flame speed correlation [6]. This may also occur with this nozzle.…”
Section: Characterizing Flow Field Developmentmentioning
confidence: 93%
“…From a practical perspective, many studies have been devoted to the adaptation of the technology to gas turbines. Flow field and emissions characteristics have been reported for various gaseous fuels, including natural gas, hydrogen, and syngas [6][7][8]. Testing of a prototype low-swirl injector for a 7MW gas turbine showed that the absence of heating of the nozzle tip due to the detached flame to be an attribute of this technology in addition to its ultra-low emissions capability [ 9].…”
mentioning
confidence: 99%